Badania trwałości płytek skrawających typu Wiper. - Stachurski, Wojciech; Midera, Stanisław (Stowarzyszenie Inżynierów i Techników Mechaników Polskich, 2013)
In the paper results concerning wear resistance of Wiper cutting inserts for selected cutting conditions are presented. In the first stage of investigation recommended by manufacturer of inserts cutting parameters have been tested. Moreover out of recommended range cutting parameters were tested too. On the base of results obtained from first stage of researches, where the smallest values of roughness parameters had been noticed, cutting parameters have been selected for wear resistance investigations. In the second stage of investigation flank wear land VBB parameters and surface roughness parameters of the machined surface of the work piece were measured. Influence of applied cutting parameters on wear resistance of cutting tool has been described.
Wear resistance investigations of wiper cutting inserts